Assessment of the awareness and practices of medical waste management among healthcare and supporting providers in Al-Graifa Rural Hospital, Obari, Libya - Om Alfadel Mohammed Zaed Mone; Eljelani Salim Saad Salim (African Journal of Advanced Pure and Applied Sciences, 2025)
This study was focused of on assessing the awareness of healthcare and other supporting providers for medical waste management (MW) and practices in Al-Graifa Rural Hospital. A cross sectional observational research was done targeting 109 samples. Verbal consent was obtained from each individual participant, and all participants asked for demographic, waste awareness, observational checklist. Participants belonged to seven departments/ wards: emergency, laboratory, radiology, pharmacy, surgery, obstetrics and gynecology, dental. Of 109 participants, 40 (36.69%) were male, and 69 (63.30%) were female; mean age was 42 years, ranged 20 to 48 years, and their age groups (20 - 25; 26-35; 36-45; >45 year), (6.4%; 18.4%; 64.2%; 11.0%), respectively. Majority 95.4% (104/ 109) of the participants received no training/ education about waste management and practices. Statistically, participants who already knew the correct waste management and practices were significantly (p<0.05) lower 11/109 (10.1%), compared to those had no knowledge 98/109 (89.90%). Interestingly, all study participants were aware that the maximum period of keeping waste inside hospital premises is 48 hours. Observational data were also recorded regarding waste segregation practices, and only 20% of the observed premises followed the standard guidelines of segregation practices. All visited departments/ wards (n=7) followed standard transportation and treatment time, before 48 hours. A significant reduction (only 20%) of the participants utilizing specific trollies for each waste type. A number of interesting differences in (WM)/ practices recorded in hospital staff targeted in this work highlighted the necessity of future research targeting broader health and medical premises in South Libya.